Stakeholder Perceptions of ICT-Enabled Tax Administration and Corporate Income Tax Collection in Iraq - Amenah Salah Jalal; Ali Jabbar Hato Alsaedi (PT. Berkah Digital Teknologi, 2026)
Purpose of the study — This study assesses stakeholders’ evaluations of ICT-enabled corporate income tax administration in Iraq across five dimensions: tax collection capability, compliance facilitation and cost reduction, tax information accessibility, administrative transparency, and administrative efficiency and effectiveness. Research Method: A quantitative cross-sectional survey used a structured 52-item questionnaire administered to 384 tax officers, corporate managers, and accountants through paper-based and online modes. Respondents were selected purposively. Data were analyzed using IBM SPSS Statistics, descriptive statistics, Cronbach’s alpha, one-sample t-tests, effect sizes, and Holm-adjusted stakeholder-group comparisons. Result— The results show that digital transformation boosts the tax authority’s access to precise and up-to-date financial information, increases corporate tax compliance, reduces compliance costs, improves the quality of government financial reports, increases the amount of corporate income tax collected, boosts transparency, and enhances the efficiency and effectiveness of the tax collection progression. Conclusion— The implementation of digital transformation has a key role in improving the quality of government financial reports and corporate income tax collection in Iraq. Increased investment in this area has directs impacts on higher tax revenues and a better financial transparency. Limitations— The study used cross-sectional, self-reported, purposively sampled data and did not measure objective changes in revenue, compliance costs, or administrative performance. Contribution— The study contributes to public administration, taxation, information systems, digital government, and management by providing a multidimensional stakeholder-based framework for evaluating ICT-enabled tax administration in an emerging-economy context.